APPLICATION OF BIOREGULATOR AND PRODUCTION OF THE COTTON PLANT AND QUALITY OF FIBER - ALBRECHT, Leandro Paiola; BRACCINI, Alessandro de Lucca e; ÁVILA, Marizangela Rizzatti; BARBOSA, Mauro Cezar; RICCI, Thiago Toshio; ALBRECHT, Alfredo Jr. Paiola (Scientia Agraria, 2009)
The objective of the work was to evaluate the yield components of the cotton culture and the quality of fiber of the cotton plant, in response to the use of a bioregulator, through treatment of seeds and application to foliate. The treatments were composed by two application forms, treatment of seeds and pulverization to foliate, in different stadiums phenologicals of the culture (V3 e B1), with the biorregulador de promotive action (0.9 g dm-3 cinetin; 0.5 g dm-3 giberellic acid; and 0.5 g dm-3 indolbutiric acid), in different doses (0, 100, 150 and 200 cm3 100 kg-1 of seeds and 0, 25, 37.5 and 50 cm3 ha-1, to foliate). The cotton productivity, fiber yield, mass of the cotton boll and fiber quality. Were evaluated all the forms of application of bioregulator increased the productivity significantly, the fiber yield, mass of the cotton boll and uniformity of the fibers and were not phytotoxic to the plants.